Pola Asuh Demokratis Ibu Tunggal dalam Mendukung Kemandirian Anak Usia 5-13 Tahun: Systematic Literature Review - Vikha Aprilia Salsabila; Syifa Nurul Alaika Sangadji; Uzrah Fadizah Tahir; Triatma Warastita Ali (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study is motivated by the increasing phenomenon of single-parent families, particularly single mothers, who carry dual roles as breadwinners and primary caregivers. This condition may influence the parenting practices applied by mothers, especially in supporting the development of children’s independence. This study aims to examine democratic parenting practiced by single mothers, the factors influencing its implementation, and its impact on the independence of children aged 5-13 years. The method used in this study is a systematic literature review by examining relevant scientific articles from national and international journals. The reviewed articles were selected based on their relevance to single mother parenting, democratic parenting, and child independence. The data were analyzed using content analysis and synthesized narratively. The findings indicate that democratic parenting is a relevant parenting style in supporting children’s independence in single-mother families. This parenting style is characterized by open communication, emotional support, clear rules, children’s involvement in simple decision-making, and the provision of responsibilities according to the child’s age and abilities. The impact of democratic parenting can be seen in children’s increased ability to take care of themselves, regulate emotions, complete tasks, make decisions, and take responsibility for their behavior. However, the implementation of democratic parenting is influenced by economic conditions, limited time, dual roles, the mother’s psychological condition, and social support. Therefore, the quality of single mothers’ parenting plays a more important role in children’s independence than family structure itself.